Comparıson Of The 2 Treatment Methods In Class Iı Dıvısıon 1 Malocclusıons - Sibel Bakır; Ayhan Enacar (Galenos Yayinevi, 1992)
In this investigation 20 patients in the mixed dentition with class II division 1 malocclusions whose dental arches are properly designed were selected as the control group. After 6 months of observation period, occuring changes were evaluated cephalometrically, and comparisons between the groups were made. At the end of the 6 months ANB angle showed a greater decrease in the monoblock group, but the skeletal profile and the interrelation between the jaws were treated better in the Teuscher group than in the monoblock group. None of the groups showed significant change in the vertical growth of the face.